Empowerment of Women Fishermen through Joint Business Groups: An Analysis of AGIL and Social Constructivism in Small-Scale Fisheries, Talisayan - M. Ichsan Rapi; Pawennari Hijjang; Ansar Arifin (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Small-scale fisheries in Indonesia significantly contribute to coastal economies and food security, yet women fishers remain marginalized due to limited access to capital, markets, and restrictive gender norms. This study analyzes how Kumpulan Usaha Bersama (KUB), or collective enterprises, function as platforms for women's empowerment in Talisayan Village, Berau Regency, East Kalimantan. Employing a qualitative case study design, data were collected through participant observation, in-depth interviews, focus group discussions, and document reviews. The analysis applied Talcott Parsons' AGIL framework and Berger & Luckmann's social constructivist theory. The findings reveal that KUB functions as: (1) an adaptation mechanism to economic pressures by providing access to microfinance, savings schemes, and livelihood diversification; (2) a means of goal attainment by enhancing household income and women's economic independence; (3) a space of integration that strengthens social solidarity, trust networks, and community social capital; and (4) an agent of latency that fosters normative change and expands women's leadership roles. Women reconstruct their identities from marginal workers to recognized economic actors through internalization, externalization, and objectivation. This study concludes that KUB improves household welfare, enhances socio-ecological resilience, and creates spaces for gender equality in coastal communities. Academically, the study expands the application of the AGIL framework and social constructivism in gender and fisheries studies. Practically, it recommends institutional strengthening, market access, and technological support as strategies for inclusive and sustainable coastal development